Novel therapies for post-stroke cognitive impairment: a systematic review - Kreiger, Katharina; Weiss, Elisabeth; Fluri, Felix (Frontiers in Neurology, 2025)
BackgroundStroke impacts 15 million people annually, ranking as the second-leading cause of mortality and the third-leading cause of disability globally. Despite advances in acute care, long-term cognitive impairments persist in 30–70% of survivors, impeding rehabilitation and increasing dependency. The existing treatments for post-stroke cognitive impairment (PSCI) show limited efficacy, underscoring the need for more comprehensive approaches. The objective of this systematic review is to evaluate the effectiveness of novel therapeutic interventions for PSCI.MethodsThe present systematic review was conducted in accordance with the PRISMA guidelines and has been registered in PROSPERO (CRD42024621445). A comprehensive search in PubMed and EMBASE identified randomized controlled trials (RCTs) from the past 5 years examining PSCI interventions, with the selection criterion being an assessment of the trials using the Montreal Cognitive Assessment (MoCA). Statistical analyses included pooled mean differences (MD) with 95% confidence intervals (CI), heterogeneity assessment, and subgroup analyses.ResultsOf 755 identified articles, 22 RCTs involving 5,100 participants met the inclusion criteria. The results demonstrated that brain stimulation therapies, particularly transcranial direct current stimulation (tDCS; MD 4.56, 95% CI: 3.19–5.93) and pharmacological interventions (MD 4.00, 95% CI: 3.48–4.52) exhibited significant benefits. Acupuncture showed potential benefits (MD 2.65, 95% CI: 1.07–4.23), albeit with considerable variability. Training approaches yielded mixed outcomes (MD 1.53, 95% CI: −0.09–3.15). Early interventions (within 3 months post-stroke) were the most effective.DiscussionBrain stimulation, especially tDCS, resulted in consistent cognitive benefits, with early initiation enhancing outcomes. Pharmacotherapy demonstrated robust, generalizable results, while cognitive training showed small but reliable effects. Acupuncture and physical training hold potential but require further standardization.ConclusionEffective stroke rehabilitation requires a multimodal, personalized approach integrating brain stimulation, pharmacotherapy, and cognitive training. Early intervention is critical for maximizing neuroplasticity, the effect of later interventions needs further evaluation. Standardization is needed to optimize physical training and alternative medicine.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024621445.